A theoretical comparison between two ruminal electron sinks - Ungerfeld, Emilio M. (Frontiers in Microbiology, 2013)
Dihydrogen accumulation resulting from methanogenesis inhibition in the rumen is an energy loss and can inhibit fermentation. The objective of this analysis was to compare the energetic and nutritional consequences of incorporating H2 into reductive acetogenesis or additional propionate production beyond the acetate to propionate shift occurring along with methanogenesis inhibition. Stoichiometric consequences were calculated for a simulated fermentation example. Possible nutritional consequences are discussed. Incorporating H2 into reductive acetogenesis or additional propionate production resulted in equal heat of combustion output in volatile fatty acids (VFA). Incorporation of H2 into reductive acetogenesis could result in moderate decrease in ruminal pH, although whole-animal buffering mechanisms make pH response difficult to predict. Research would be needed to compare the microbial protein production output. There could be post-absorptive implications due to differences in VFA profile. Electron incorporation into reductive acetogenesis could favour energy partition towards milk, but increase risk of ketosis in high-producing dairy cows on ketogenic diets. Greater propionate production could favour milk protein production, but may be less desirable in animals whose intake is metabolically constrained, like feedlot steers. Because of the different nutritional implications, and because practical solutions to incorporate H2 into either pathway are not yet available, it is recommended to research both alternatives.